Prevalence, risk factors, and outcomes of acute kidney injury in a cardiac intensive care unit patients: a comprehensive study in a tertiary care setting - Naidu, Sirapurapu Veera Venkata Laxmaiah; Ashraf, Shehla; Kukunoor, Hanisha R.; Arvindbhai, Deep Gorfad; Gohil, Aastha Rameshbhai (International Journal of Research in Medical Sciences, 2025)
Background: Acute kidney injury (AKI) is a frequent and serious complication among critically ill patients in the intensive care unit (ICU), contributing to increased morbidity, mortality, and prolonged hospitalization. This study aimed to assess the prevalence of AKI and identify associated risk factors among ICU patients at Government General Hospital (GGH), Srikakulam. Methods: A descriptive cross-sectional study was conducted over one year in the nephrology ICU at GGH, Srikakulam, Andhra Pradesh. Data from 150 adult ICU patients were retrospectively reviewed. Patients with chronic kidney disease or prior kidney transplantation were excluded. Information on demographics, comorbidities, AKI diagnosis (based on KDIGO criteria), treatment, and outcomes was collected. Statistical analysis was performed to determine significant risk factors for AKI. Results: AKI was diagnosed in 74 patients (49.3%). The mean age of AKI patients was 65.4 years, significantly higher than non-AKI patients (58.6 years, p=0.001). Hypertension was more common among AKI patients (50% versus 29%, p=0.02), and sepsis was present in 60% of AKI cases compared to 19.4% in non-AKI patients (p=0.001). AKI patients had longer ICU stays (14.8 versus 8.9 days, p=0.001) and higher mortality (46.7% versus 16.1%, p=0.001). Conclusions: AKI is highly prevalent in ICU patients and is significantly associated with older age, hypertension, and sepsis. It correlates with longer ICU stays and increased mortality. Early recognition and targeted management of risk factors are crucial to improving outcomes in critically ill patients.